Women, agriculture, and villages: A community of empowerment study to achieve wellbeing and sustainable development - Arintyas, Ameylia Puspita Rosa Dyah Ayu (Journal of Agrosociology and Sustainability, 2024)
Background: The women farmers play a crucial role in Indonesian villages. It needs the empowerment model for addressing the challenges and opportunities so the women farmers can increase her capacity especially in the agriculture system and family quality. By this condition we conduct research that focuses on the process of empowerment to achieve wellbeing and sustainable development. Method: Data drawing on a literature review, best practices, and real-life narratives. Findings: The data shows that despite their significant contribution to agriculture, women farmers are facing a lack of resources like land, credit, and information. Social norms build can relegate them to less demanding tasks, while decision-making power frequently resides with men. These persistent gender biases hinder their full potential and limit their agency. The narrative analysis reveals the remarkable resilience of women farmers. They manage their farms efficiently, innovate to adapt to changing circumstances, and find purpose and well-being through their work.  The stories showcase their crucial role in rural economies and their capacity to overcome limitations. The research identifies key areas to empower women farmers and achieve sustainable development. Conclusions: Investing in their well-being through access to healthcare, childcare, and financial security empowers them to invest in themselves and their families.  Promoting sustainable practices through training programs equips them with the tools to nurture the land for future generations.  Fostering knowledge sharing and collaboration creates a network for innovation and best practices to flourish.  Finally, breaking down gender barriers and promoting women's leadership in agriculture is crucial for achieving true empowerment and a more equitable future. By prioritizing the well-being of women farmers and fostering sustainable practices, we can create a virtuous cycle. Empowered women farmers contribute to a more secure and nourishing future, not just for themselves and their families, but for the entire community and the environment they sustain. Investing in women farmers is an investment in a future where well-being and sustainability go hand in hand. Novelty/Originality of this Study: This study employs a multi-faceted approach to empower rural women farmers in Yogyakarta, Indonesia. By integrating qualitative data from in-depth interviews and document analysis, it uncovers the intricate interplay between gender, agriculture, and rural development. Ultimately, the research highlights the critical role of tailored empowerment strategies in enhancing the economic, social, and environmental resilience of these women.